The effects of application of biochar from oil palm empty fruit bunches on chemical properties of ultisols and the growth of cacao seedlings - Sari, Wulan Kumala; Malik, Panji Abdul (Universitas Padjadjaran, 2023)
It is necessary to redevelop cacao (Theobroma cacao L.) commodity due to the decrease of cacao planting areas in Indonesia since the last decade. One of the ways is by providing a growing medium to produce cacao seedlings with good quality, such as by adding ameliorant i.e., oil palm empty fruit bunch (OPEFB) biochar to marginal soil of Ultisols. This research aimed to study and obtain the best OPEFB biochar dose to improve the chemical properties of Ultisols and the growth of cacao seedlings. This research was conducted in the Experimental Field of the 3rd Campus Andalas University from August 2021 until February 2022 using a Completely Randomized Design (CRD) with 5 treatments of OPEFB biochar (0, 60, 90, 120, 150 tons/ha) and 4 replications, each experimental unit consisted of two plants, so that 40 plants were prepared in total. Data obtained were analyzed using F Distribution Test at 5% and further analyzed using Duncan’s New Multiple Range Test (DNMRT) for statistically significant results. The results showed that the application of OPEFB biochar at 120 tons/ha was the best dose to give significant results on the chemical properties of Ultisols (pH, organic carbon, total nitrogen, available phosphorus, exchangeable potassium) and several growth variables of cacao seedlings (stem diameter, leaf length, leaf width, shoot dry weight, and shoot-root ratio).Keywords: ameliorant, biochar, nursery, oil palm empty fruit bunch, Ultisols